2010
DOI: 10.1007/s00044-010-9371-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antitumor activity of (4-hydroxyphenyl)[5-substituted alkyl/aryl)-2-thioxo-1,3,4-thiadiazol-3-yl]methanone and [(3,4-disubstituted)-1,3-thiazol-2ylidene]-4-hydroxybenzohydrazide

Abstract: To examine new drug leads with potential anticancer activity, some (4-hydroxyphenyl)[5-substituted alkyl/aryl)-2-thioxo-1,3,4-thiadiazol-3-yl]methanone (4.a-4.c) and [-(3,4-disubstituted)-1,3-thiazol-2ylidene)]-4-hydroxybenzohydrazide (6.a-6.d) were synthesized using appropriate synthetic route. The newly prepared compounds 4.a-4.c and 6.a-6.d demonstrated inhibitory effects on the growth of a wide range of cancer cell lines especially on leukemia (HL-60), non-small lung cancer (HOP-92), renal cancer (ACHN) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 22 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…Compound (4‐hydroxyphenyl)[5‐(2,6‐dichloro)‐2‐thioxo‐1,3,4‐thiadiazol‐3‐yl]methanone ( 42 ) showed broad spectrum of growth inhibition activity against human tumor cells and remarkable cytotoxic activity on nonsmall lung cancer (HOP 92) having log GI 50 value at ‐6.49, colon cancer (HCC‐2998) at GI 50 value −5.31 and significant cytotoxic activity on prostate cancer (PC‐3) having GI 50 value −5.48. SAR study revealed that electron withdrawing group at position C‐5 of thiadiazol was favorable for activity .
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound (4‐hydroxyphenyl)[5‐(2,6‐dichloro)‐2‐thioxo‐1,3,4‐thiadiazol‐3‐yl]methanone ( 42 ) showed broad spectrum of growth inhibition activity against human tumor cells and remarkable cytotoxic activity on nonsmall lung cancer (HOP 92) having log GI 50 value at ‐6.49, colon cancer (HCC‐2998) at GI 50 value −5.31 and significant cytotoxic activity on prostate cancer (PC‐3) having GI 50 value −5.48. SAR study revealed that electron withdrawing group at position C‐5 of thiadiazol was favorable for activity .
…”
Section: Methodsmentioning
confidence: 99%
“…48. SAR study revealed that electron withdrawing group at position C-5 of thiadiazol was favorable for activity [37]. (47), with ID 50 two times lower (SW707, T47D) than that of cis-platin displayed the highest cytotoxicty.…”
mentioning
confidence: 99%
“…To obtain 4-amino-3-mercapto-1,2,4-triazole intermediates 8a-i, first the acid hydrazide 6 was prepared from ethyl ester 5 by treating with hydrazine hydrate in absolute ethanol [19]. The acid hydrazide 6 was allowed to react with carbon disulphide in the presence of potassium hydroxide in methanol to give the corresponding potassium dithiocarbazinate 7.…”
Section: Designed Compoundsmentioning
confidence: 99%
“…The key intermediates 4 and 8 were synthesized according to the literature [18,19,[21][22][23]. Commercial solvents were used without any pretreatment.…”
Section: Chemistrymentioning
confidence: 99%
“…Thiazole ring is an important pharmacologically active heterocylic ring whose mono-, di-, three-substituted, condensed derivatives and reduced analogs (thiazoline, thiazolidine) have been widely studied in medicinal chemistry [ 1 , 2 , 3 , 4 , 5 , 6 ]. Among these molecules with common origin, thiazoline derivatives have attracted attention due to existing in many biochemical reactions in organisms [ 7 ]. Consequently, various thiazoline derivatives were reported with a broad spectrum of activity attributed to this property [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%